School Principal Supervision Management in Improving the Competency of Class Teachers at SD Inpres Maliambao - Korompot, Sudarmin (International Journal Labs, 2023)
The research aims to analyze the competence of class VI teachers, the principal's academic supervision in increasing the competence of class VI teachers, and the implications of the principal's academic supervision in increasing the competence of class teachers. This research is a qualitative descriptive research that uses a pedagogical and managerial approach. The data source, namely primary data, comes from the principal, deputy principal, and teachers through interviews. Meanwhile, secondary data is taken from documents related to the research. The results of the research show that the Class VI teacher at SD Inpres Maliambao has good mastery of textual material, but is less able to illustrate it contextually. Mastery of Competency Standards/Basic Competencies (SK/KD) is adequate, but lacking in developing attitude and skill indicators. The development of learning materials and strategies is still limited, as well as professional development which is still pending, and the use of technology and information is very limited. School principals' academic supervision involves preparing a needs-based supervision program, implementing programs with a focus on fostering learning planning, contextual material guidance, fostering mastery of basic competencies, innovative learning strategies, professional development through writing scientific papers, and utilizing technology and information. Evaluation and follow-up of the supervision program is an integral part of this process. The implications of principal supervision involve increasing the professional competence of classroom teachers, positive responses from students and schools towards teachers with high competence, as well as positive responses from teachers towards school principals.